Pemarkah Stansial dalam Buku Biografi Gus Dur Serta Implementasinya Terhadap Pembelajaran Teks Biografi Kelas X - Maiza Abidah Utami; Ahmad Fadly (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
A biography book is a written work that is compiled based on factual events about a person's life, but writers are often faced with the choice of how to represent the reality surrounding the characters they are telling. In the process of writing, a writer not only gathers facts, but also interprets and highlights certain aspects of the character's life. This can be seen through the way language is used, including standard markers, which reflect the author's attitude and position towards the facts raised. This research aims to analyze the author's attitude towards this reality, as reflected through the use of stationary markers in the biography of President Abdurrahman Wahid (Gus Dur) by Greg Barton. This study uses a descriptive qualitative approach with a content (text) analysis method. The source of research data is in the form of Gus Dur's biographical text which is analyzed by referring to five categories of standard markers, namely hedges, boosters, attitude markers, self-mentions, and engagement markers. Each category provides an overview of how the author conveys an argument, expresses an attitude, and builds a closeness with the reader. The results of the study show that the use of boosters dominates, which illustrates the author's firm attitude in emphasizing facts and assessments of Gus Dur. In addition, the word